Thermal-hydraulic analysis of a research reactor on personal computer with TARR code - Can, Ngo Huy; Lan, Nguyen Manh; Tran, Tran Van (Vietnam Journal of Mechanics, 1992)
The code has been created for thermal-hydraulic calculation of stationary regime of nuclear research reactor, using personal computer. The main objective of the code is to compute the thermal parameters in the reactor core in order to avoid any accident. The code can be applied for many fuel assemblies available in research reactors.